2019
DOI: 10.1111/rda.13571
|View full text |Cite
|
Sign up to set email alerts
|

Extenders modify the seminal plasma ability to minimize freeze‐thaw damage on ram sperm

Abstract: Seminal plasma (SP) proteins interact with sperm plasma membrane (PM) modulating its functionality. It has been shown that SP proteins can reverse the damage caused by freeze‐thaw; however in these studies, SP has been added to washed sperm (i.e., cells depleted from homologous SP and extender). The aim of the current study was to assess whether the egg yolk‐based extender (EY) modifies SP ability to ameliorate sperm parameters in frozen‐thawed ram spermatozoa. Ejaculates were diluted in EY or soybean lecithin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…In our study, we used concentrations (i.e., 0, 125, 250, and 500 µg/mL) based on a previous study that used a bovine model [ 40 ]. Results from different studies indicate that adding SP to proteins could have both positive and negative effects on the quality of cryopreserved spermatozoa [ 14 , 15 , 16 , 41 ]. The effect of SP proteins is very complex and has not been fully understood yet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we used concentrations (i.e., 0, 125, 250, and 500 µg/mL) based on a previous study that used a bovine model [ 40 ]. Results from different studies indicate that adding SP to proteins could have both positive and negative effects on the quality of cryopreserved spermatozoa [ 14 , 15 , 16 , 41 ]. The effect of SP proteins is very complex and has not been fully understood yet.…”
Section: Discussionmentioning
confidence: 99%
“…These processes result in changes in lipid composition and consequently in decreased PM fluidity and permeability [ 9 ], leading to premature capacitation-like and acrosome reaction-like changes in sperm [ 10 ]. Currently, in bulls, boars, and rams, it seems that the mentioned negative effects of cryopreservation can be reduced by adding a certain amount of SP or particular components thereof to the suspension (spermatozoa + extender) during processing [ 6 , 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zalazar et al [150] reported that addition of heterologous SPINK3 before or after freezing-thawing decreased protein tyrosine phosphorylation and intracellular calcium influx in ram sperm. However, other sperm parameters related to sperm quality and fertility only improved when this recombinant protein was added after cryopreservation, probably due to the interaction of SPINK3 with extender components such as egg yolk before freezing, which may alter the ability of this protein to reduce sperm cryodamage [151].…”
Section: Molecular Aspects Of Those Novel Strategies To Reduce Sperm mentioning
confidence: 99%
“…Beyond the spermatozoa themselves, the complex, proteindominated, milieu comprising the seminal plasma has also received considerable attention it terms of its capacity to stabilize and reduce stress on the sperm membrane thereby preventing damage incurred during cryo-/liquid-preservation [56,[64][65][66] An important component of this milieu are the EVs that originate from accessory sex glands or upstream in the testis and epididymis. [28] The most widely studied of these EVs are prostasomes, which are secreted from the prostate epithelial cells and thereafter interact with spermatozoa to modulate their function and afford protection against the immune defences encountered within the female reproductive tract.…”
Section: Discussion Of Findingsmentioning
confidence: 99%